2017
DOI: 10.1021/acs.joc.7b00481
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Approaches to the In Situ Generation of Anhydrous Tetraalkylammonium Fluoride Salts for SNAr Fluorination Reactions

Abstract: This article focuses on the development of practical approaches to the in situ generation of anhydrous fluoride salts for applications in nucleophilic aromatic substitution (SAr) reactions. We report herein that a variety of combinations of inexpensive nucleophiles (e.g., tetraalkylammonium cyanide and phenoxide salts) and fluorine-containing electrophiles (e.g., acid fluoride, fluoroformate, benzenesulfonyl fluoride, and aryl fluorosulfonate derivatives) are effective for this transformation. Ultimately, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…We hypothesize that fluorosulfation is the rate-limiting step instead of the SO 2 F 2 generation from SDI. 13 C NMR confirmed that SDI completely decomposed in less than 30 s under the optimized reaction conditions (see SI). It was also shown that under these circumstances, the actual pressure inside the vessel remained well under the maximally allowed internal pressure (see SI).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…We hypothesize that fluorosulfation is the rate-limiting step instead of the SO 2 F 2 generation from SDI. 13 C NMR confirmed that SDI completely decomposed in less than 30 s under the optimized reaction conditions (see SI). It was also shown that under these circumstances, the actual pressure inside the vessel remained well under the maximally allowed internal pressure (see SI).…”
mentioning
confidence: 71%
“…Furthermore, aryl fluorosulfates are also versatile intermediates as they can be converted into aryl fluorides, 10 aryl sulfamate esters, 11 and others 12 or can even be used for the synthesis of anhydrous tetraalkylammonium fluoride salts. 13 Historically, aryl fluorosulfates are mainly synthesized via four different approaches. 14 The first method relies on the pyrolysis of arenediazonium fluorosulfate salts.…”
mentioning
confidence: 99%
“…However, the preparation of quaternary ammonium fluorides is always accompanied with hydration of the fluoride ions, which would decrease the nucleophilicity of fluoride ions as well as cause further transformation and side reactions [28]. To avoid the impact of water on the S N Ar fluorination reactions, either predried [29] or in situ prepared [30][31][32] anhydrous quaternary ammonium fluorides have been used to achieve high yields of the (hetero)aryl fluorides. The results with these anhydrous quaternary ammonium fluoride salts compare favorably to traditional S N Ar fluorination using alkali metal fluorides, which generally require temperatures at higher than 100 C [7].…”
Section: S N Ar Fluorination With Quaternary Ammonium Fluoridesmentioning
confidence: 99%
“…The formation of the side products is nearly completely suppressed at this low reaction temperature. In addition, anhydrous TMAF in situ generated from inexpensive nucleophiles (such as tetramethylammonium cyanide and phenoxide salts) and fluorine-containing electrophiles (such as acid fluoride, fluoroformate, benzenesulfonyl fluoride, and aryl fluorosulfonate derivatives) can be used for the same purpose with excellent results [30].…”
Section: S N Ar Fluorination With Quaternary Ammonium Fluoridesmentioning
confidence: 99%
“…Sanford and co‐workers reported that 4‐methoxyphenyl sulfurofluoridate ( 2 ) reacted with tetramethylammonium 2,6‐dimethylphenoxide in DMF for 15 min at room temperature to afford 2,6‐dimethyl phenyl(4‐methoxyphenyl)sulfate ( 113 ; Scheme ) …”
Section: Chemical Transformationsmentioning
confidence: 99%